Kinetics and Mechanism of Oxidation of Indigocarmine by N-Sodio-N-Bromobenzenesulphonamide (Bromamin-B) in Acid Buffer Medium - Ananda, S.; J.D. Saldanha, Ravi; Venkatesha, B.M. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of indigocarmine [IC] by bromamine-B inpH 5 buffer medium has been studied at 30°C spectrophotometricallyat λmax 610 nm. The reaction is first order with respect to [IC]and second order with respect to [BAB]. The reaction rate showsan inverse first order on [benzenesulphonamide].. Addition of halideions and variation of ionic strength of the medium have no influenceon the reaction rate. There is a negative effect of dielectric constantof the solvent. Activation parameters have been calculated. Mechanismproposed and the derived rate laws are consistent withobserved kinetics.